PSYCHOMOTOR PATTERN FOR NEUROLOGICAL ASSESSMENT OF REFLEX IN KARATE AND TAEKWONDO: Manual muscle test under load – general model - Savić, Radoš; Kalinović, Maja (Sport - nauka i praksa, 2022)
A reflex is an involuntary reaction of the nervous system to intrinsic and extrinsic stimuli. In athletes, it is largely damaged, which presents a serious problem. The psychomotor pattern for the neurological assessment of reflex in karate, taekwondo and other martial arts is based on the principles of physiology, neurology and biomechanics. Pattern can be defined as an inseparable entity of the physical (motor), psychological (mental-emotional) and energy factor, during manual muscle test under load used to assess muscle tonus, which is the subject of this paper. The aim of the paper is to determine neurological reflex activities of athletes’ muscles when they are subject to load in order to fully exploit their potential. Investigating the reaction of the peripheral nervous system was based on the assessment of examinees’ reflexes, among which were active athletes N = 50 and random sample of examinees N = 50, as well as on data comparison. The results indicated the damaged muscle innervation in 46% of athletes and 50% of random sample of examinees. The conclusion is that muscle tone virtually does not depend on whether someone is engaged in sport or not, and on the other hand, it sends a warning that it is necessary to balance the nervous system. Therefore, by restoring biological feedback, an adequate reaction of the nervous system improves health and athletes’ training process. The authors provide a model of pre-exercise testing, which has the basic role of preventing muscle tone and a key role as a guardian of natural human functioning.